Optimization of the Level of Tapioca Starch in Chicken Meat Caruncles - Singh, Parminder; Sahoo, Jhari; Chatli, Manish K.; Biswas , Ashim K. (Journal of Meat Science, 2014)
The present study was conducted to optimize the level of tapioca starch for the development of chicken meat caruncles (CMC). Three different levels of tapioca starch replacing - 50% (T-1), 60% (T-2) and 70% (T-3) of refined wheat flour, were undertaken along with control (100% refined wheat flour) for this study. All the variants were assayed for physico-chemical, proximate composition, texture profile, colour profile and sensory attributes. The cooking yield (%) was significantly higher (P<0.05) in T-2 than control group. Hydratability of T-3 sample was significantly lower (P<0.05) than control and T-1. Water absorption index of control samples was significantly lower (P<0.05) than the treated samples. The fat (%) of T-1 was significantly higher (P<0.05) than T-2 and T-3. Crude fiber (%) was found to be significantly lower (P<0.05) in T-1 than T-2 and T-3 samples. Hardness of T-2 was significantly higher (P<0.05) than control. There was no significant variation between adhesive force and stringiness of control, T-1, T-2 and T-3 samples. In colour profile, the L* and a* value of control was significantly lower (P<0.05) than T-1, T-2 and T-3 samples. Among the sensory attributes colour, flavour, crispiness, after-taste and meat flavour intensity were non-significant between control and treated batches. Overall acceptability was significantly higher (P<0.01) at 60% tapioca starch replacement level (T-2) as compared to others. On the basis of sensory quality, 60% incorporation of tapioca starch in place of refined wheat flour was adjudged as optimum in chicken meat caruncles